Dynamic bandwidth allocation algorithm based on transmission rate adaptation - Geng CHEN; Wei-wei XIA; Lian-feng SHEN (Tongxin xuebao)
A dynamic bandwidth allocation algorithm was proposed based on the transmission rate adaptation to guaran-tee the quality of service (QoS) for multi-service in heterogeneous wireless network. According to the proposed transmis-sion rate priority decision model, an optimal bandwidth reallocation matrix was obtained by dynamically adjusting users' transmission rates to maximize the utility function of entire heterogeneous network under the transmission rate QoS re-quirements and capacity constraints. The adaptive bandwidth reallocation problem was formulated as an optimal problem and a dynamic optimal iterative procedure was used to adjust adaptively users' transmission rates to further maximize this utility function. The results of theoretical analysis and numerical simulation show that the proposed algorithm can maxi-mize the network utility function and reduce the new calls blocking probability as well as guaranteeing the transmission rate and QoS requirements.